Balo's concentric lesions with concurrent features of Schilder's disease in relapsing multiple sclerosis: neuropathological findings - Maher Kurdi; David Ramsay (University of São Paulo, 2016)
Atypical inflammatory demyelinating syndromes are rare neurological diseases that differ from multiple sclerosis (MS), owing to unusual clinicoradiological and pathological findings, and poor responses to treatment. The distinction between them and the criteria for their diagnoses are poorly defined due to the lack of advanced research studies. Balo's concentric sclerosis (BCS) and Schilder's disease (SD) are two of these syndromes and can present as monophasic or in association with chronic MS. Both variants are difficult to distinguish when they present in acute stages. We describe an autopsy case of middle-aged female with a chronic history of MS newly relapsed with atypical demyelinating lesions, which showed concurrent features of BCS and SD. We also describe the neuropathological findings, and discuss the overlapping features between these two variants